PENGARUH POSITIVE LEADERSHIP, SOCIAL CAPITAL PADA EMPLOYEE WELL-BEING - Eva Nur Rachma (Fakultas Ekonomi Universitas 45 Surabaya, 2016)
The economic growth will be continues to grow, many companies to try making survive to sustain and go out from insolvent. With the involvement of social capital and labor that goes well and supports active participation in the work environment will be created in the organization's strong commitment to both performance and survival of the organization itself. This research is causality (cause-effect) by using a quantitative approach. Object of research that all employees in PT. Bahama Swastika, the population and the sample amounted to 101 employees as sample. Data were analyzed using SPSS version 13.0.The results showed that positive leadership and social capital affect of the employee well-being, positive leadership and social capital simultaneously influence on employee well-being.